A laboratory study of high-performance cold mix asphalt mixtures reinforced with natural and synthetic fibres. (30th May 2018) - Shanbara, Hayder Kamil; Ruddock, Felicite; Atherton, William
Highlights: Novel cold mix asphalt mixtures reinforced using natural fibres. Significant improvement in mechanical properties of the reinforced CMA is revealed. Mechanical properties of the reinforced CMA are comparable to the HMA. Abstract: This research aims to examine the impact of using natural and synthetic fibres as reinforcing materials, on the mechanical properties and water susceptibility of cold mix asphalt (CMA) including indirect tensile stiffness and resistance to rutting, cracking and moisture damage. Four different types of fibres were used: glass as a synthetic fibre, and hemp, jute and coir as natural fibres. Various samples of CMA, with and without fibres, were fabricated and tested. Traditional hot mix asphalt (HMA) was also used for comparison. The results indicate a significant improvement in the indirect tensile stiffness modulus, for all fibre-reinforced CMA mixtures, over different curing times. The improved tensile behaviour represents a substantial contribution towards slowing crack propagation in bituminous mixtures, while scanning electron microscopy analysis confirmed the fibre shape and surface roughness characteristics. The improved performance of the reinforced mixtures with both natural and synthetic fibres, facilitated a substantially lower permanent deformation than traditional hot and cold mixtures at two different temperatures (45 °C and 60 °C). When using glass and hemp fibres as reinforcing materials, there was a significant improvement in CMA in terms of water sensitivity. Resistance to surface cracking was also improved when fibres were incorporated. Based on the test results, 0.35% fibre content by mass of dry aggregate and 14 mm fibre length are recommended to achieve the optimum performance output for indirect tensile stiffness.